2014
DOI: 10.14507/epaa.v22n81.2014
|View full text |Cite
|
Sign up to set email alerts
|

A escolarização de pessoas com deficiência intelectual no Brasil: da institucionalização às políticas de inclusão (1973-2013)

Abstract: A escolarização de pessoas com deficiência intelectual no Brasil: da institucionalização às políticas de inclusão (1973-2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 3 publications
0
8
0
14
Order By: Relevance
“…Silveira and Neves (2006) interviewed 10 families and 10 teachers of children with disabilities and found that the participants questioned the benefits of including these students in regular classes, often due to the lack of structures in public schools to meet their learning needs. Pletsch (2014aPletsch ( , 2014b found similar results about the AEE service and the low literacy rates of the special education population since "students with more severe or multiple disabilities, despite being enrolled in regular education, end up attending the multifunctional resource room for only one hour, two or three times a week" (Pletsch, 2014a, p. 17), i.e., they only attend AEE. After analyzing interviews with teachers and school administrators and footage of the pedagogical practices applied in AEE rooms, Pletsch (2014b) concluded that many students with ID ended up being sent to youth and adult education classes (type of education for students who, for whatever reason, have not completed basic and/or secondary education within the appropriate age) after years in regular classes without learning how to read and write.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Silveira and Neves (2006) interviewed 10 families and 10 teachers of children with disabilities and found that the participants questioned the benefits of including these students in regular classes, often due to the lack of structures in public schools to meet their learning needs. Pletsch (2014aPletsch ( , 2014b found similar results about the AEE service and the low literacy rates of the special education population since "students with more severe or multiple disabilities, despite being enrolled in regular education, end up attending the multifunctional resource room for only one hour, two or three times a week" (Pletsch, 2014a, p. 17), i.e., they only attend AEE. After analyzing interviews with teachers and school administrators and footage of the pedagogical practices applied in AEE rooms, Pletsch (2014b) concluded that many students with ID ended up being sent to youth and adult education classes (type of education for students who, for whatever reason, have not completed basic and/or secondary education within the appropriate age) after years in regular classes without learning how to read and write.…”
Section: Introductionmentioning
confidence: 87%
“…According to Pletsch (2014a), the growing number of legal devices that organized and guided school practices for the process of school inclusion led to a gradual increase in the number of students with disabilities enrolled in the regular education network. In a study with 24 relatives of students with ID aged between 9 and 29 years, of whom a third were illiterate, Lima, and Mendes (2011) identified the following parents' reasons for enrolling their children in regular school: first, learning and development in general; second, socialization; and third, literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the current reality of educational policies for inclusion in Brazil, as well as the reality of Brazilian public schools, as pointed by the INEP Census in 2016, this finding reveals a gap in the qualitative aspects of Brazilian basic education 7-9 , despite achievements regarding the school inclusion of individuals with SN 1-3 guaranteed by national legislation 4,5, [14][15][16][17][18][19] .…”
Section: Total Papers Retrieved 214mentioning
confidence: 99%
“…De acordo com Pletsch (2014), essa evolução no atendimento educacional das pessoas com deficiência, primordialmente, está pautada no reconhecimento delas enquanto cidadãs plenas de direitos e deveres sociais iguais e inalienáveis. Mais especificamente no contexto brasileiro, pode-se assegurar que tanto os estudos científicos, quanto as políticas públicas e ações governamentais para a educação especial/inclusiva são bastante recentes e ainda mais o são na educação superior.…”
Section: Introductionunclassified
“…É preciso perceber que a inclusão educacional da pessoa com deficiência depende, antes de qualquer coisa, do seu reconhecimento como pessoa e das suas potencialidades, apesar de apresentar necessidades especiais (PLETSCH, 2014). No caso dos participantes da pesquisa, parece-nos que a não valorização e/ou descrédito no desenvolvimento acadêmico dos alunos com deficiência manifestos deve-se ao fato desses profissionais não estarem preparados profissionalmente para atuar com esta parcela minoritária da sociedade.…”
unclassified